(untitled) (International Scientific Journal Alfraganus, 2024)
This article discusses the development of fast-strength qualities of wrestlers aged 16-18 years, their special fast-strength qualities, methods of their development, the development of physical activity in training sessions, and research of the training process. according to the way they develop.